The systematics and phylogeny of the Devonian subfamily Asteropyginae (Trilobita: Phacopida) - Bignon, Arnaud Marcel Jacques (2014)
Traditionally, the evolutionary scenarios of Asteropyginae have been organized in two major clades involving four pygidial patterns. The first cladistic analysis performed on the subfamily maintained the organization in two clades, though the phylogenetic relationships between genera were unexpected compared to the traditional scenarios. Moreover, the previous systematic scheme based on pygidial segmentation was rendered obsolete. In this study, we performed a new phylogenetic analysis from well-known taxa and recent discoveries. Sixty species assigned to 36 genera have been analysed from a dataset of 72 characters. Three more species are used as the outgroup. The 79 most parsimonious trees have a length of 492 steps and a retention index of 0.735. Our analysis confirms the monophyly of Asteropyginae excluding the genus Protacanthina. The phylogenetic pattern is unconventional in that a largely pectinate topology is resolved, rather than two clades corresponding to formerly delimited pygidial morphs. Nevertheless, most relationships between genera suggested in the traditional evolutionary scenarios of the subfamily have been recovered, the main differences being the origin of the group. Whereas Treveropyge was usually considered as the origin of the remaining Asteropyginae, the present results instead identify Destombesina as the sister group to all remaining members of the subfamily. From the new phylogenetic pattern, the diagnoses of genera are rewritten in a standard way and to delimit clades more accurately. This work implies modified generic assignments for some species and the erection of four new genera: Minicryphaeus gen. nov., Gandlops gen. nov., Morzadecops gen. nov. and Pennarbedops gen. nov. The systematic position of Erbenochile is also discussed, the genus no longer being assigned to Asteropyginae.